Peranan Pendidikan Agama Islam Dalam Menjaga Kerukunan Umat Beragama - Fauzul Averoezy (Atta'dib Jurnal Pendidikan Agama Islam, 2021)
ABSTRACTWith all the diversities that the Indonesian people have, tolerance between religious communities is so important for its existence in thecommunity. The realization of religious tolerance in the community notonly brings peace in the surrounding environment but is also an effort toprotect and maintain the integrity of this nation. In order to foster aculture of tolerance, various efforts have been made by the governmentby providing and requiring general education in schools, such as IslamicEducation, Citizenship Education, and so on. The existence of religiouseducation itself is nothing but the success of the goal of shaping thecharacter of the Indonesian people from elementary school to highereducation, as individuals who are not only intelligent in terms of theory,but also noble in character. This study aims to describe inter-religioustolerance, explain the facts of religious tolerance in school, and describethe role of Islamic religious education in schools on the growth of religioustolerance. The research was conducted using a qualitative descriptiveresearch method because it is considered suitable with the theme of thisresearch. This research method was carried out by distributingquestionnaires through social media to respondents in Google Formformat. From the results of the research, it is found that the culture oftolerance that exists in Indonesia is still in the mediocre category and itspresence in society has not made an impression. The majority ofrespondents stated that they had never experienced intolerance behaviorand had never seen the incident, which means that the attitude ofintolerance in Indonesia is relatively small. From this study it can beconcluded that the role of general education such as Islamic ReligiousEducation is important in supporting the growth of inter-religiousharmony in society.Keywords: Tolerance, culture, nation, religion.